Manufacturing audit to improve quality performance - a conceptual framework - Edly Ferdin Ramly, author; Sha'ri Mohd. Yusof, author; Jafri Mohd. Rohani, 1966-, author; World Engineering Congress (2007: Pulau Pinang) (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL